2020
DOI: 10.1186/s12903-020-01253-w
|View full text |Cite
|
Sign up to set email alerts
|

The status and associated factors of early childhood caries among 3- to 5-year-old children in Guangdong, Southern China: a provincial cross-sectional survey

Abstract: Background Dental caries of deciduous teeth (Early Childhood Caries, ECC) has become a crucial oral health problem over the decades in China. The aim of this study was to examine the prevalence and severity of ECC among preschool children from Guangdong Province, Southern China. In addition, to assess the association of ECC with reported oral health-related behaviors. Methods A cross-sectional survey of 2592 participants was carried … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 28 publications
5
28
2
1
Order By: Relevance
“…The difference between the urban and rural areas was not found to be significant, which may be related to the small economic disparity between the urban and rural areas based on administrative divisions randomly selected in Guizhou, where the overall economy is not developed (11). Compared with the prevalence rate of 50.3% (dmft = 1.92) among 5-year-old children in the Third Oral Epidemiological Survey in 2005, both caries prevalence and severity are on the rise, and this phenomenon also appears in the eastern regions of China such as Jiangsu Province and Guangdong Province (12), central regions such as Henan Province, and the western regions such as Sichuan Province (13). However, the trend of change of caries in deciduous teeth during the decade of 2005-2015 in Beijing faced a rapid increase where the rate of caries was curbed after intervention (14).…”
Section: Discussionmentioning
confidence: 99%
“…The difference between the urban and rural areas was not found to be significant, which may be related to the small economic disparity between the urban and rural areas based on administrative divisions randomly selected in Guizhou, where the overall economy is not developed (11). Compared with the prevalence rate of 50.3% (dmft = 1.92) among 5-year-old children in the Third Oral Epidemiological Survey in 2005, both caries prevalence and severity are on the rise, and this phenomenon also appears in the eastern regions of China such as Jiangsu Province and Guangdong Province (12), central regions such as Henan Province, and the western regions such as Sichuan Province (13). However, the trend of change of caries in deciduous teeth during the decade of 2005-2015 in Beijing faced a rapid increase where the rate of caries was curbed after intervention (14).…”
Section: Discussionmentioning
confidence: 99%
“…Maxillary central incisors had the highest caries incidence among all the teeth in the caries-free participants at baseline, which also explains the results shown in Figure 3 that those without baseline caries were most likely to have two teeth decayed simultaneously once new caries occurred. It has been suggested that focusing on the prevention of caries of maxillary central incisors in baseline caries-free children may improve the caries-free rate of preschoolers 2 , 19 and improve the efficiency of caries prevention. Caries of the central incisors are caries that affect smooth surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Caries in deciduous teeth, unlike those in permanent teeth, usually affect smooth surfaces, followed by pits and fissures. 2 Caries of the maxillary central incisors are often nursing caries. 20 However, children with caries at baseline are a high-risk group, and the caries incidence of mandibular first deciduous molars was obviously the highest, and the caries incidence in the other teeth was not low either.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant caries index (SiC) is computed based on the mean dmft of one-third of the sample with the highest caries experience scores [ 22 , 23 ]. It is useful for identifying variations in decay proportions alongside the dmft [ 24 ], especially in countries where the overall decay experience is low [ 24 , 25 ]. SiC resolves the problem related to skewed caries distribution when using the dmft/dmfs.…”
Section: Introductionmentioning
confidence: 99%